Memorizing with the Heart, Educating with Values: Strategies and Impact of Al-Qur'an Memorization Learning at MTs Tarbiyatul Banin - Hilda Lailatul Mufida; Eko Sumadi (The Magister of Islamic Education IAIN Pontianak, 2025)
This study aims to investigate in depth the strategies, implementation, and impact of the Al-Qur'an tahfidz learning program at MTs Tarbiyatul Banin. This study uses a qualitative approach with a case study design to gain an in-depth understanding of the phenomenon under study. Data collection techniques included participatory observation, in-depth interviews, and analysis of relevant documents. The findings showed that the tahfidz learning strategy was developed with a planned strategy through the routine application of the talaqqi, ziyadah, murojaah, and tasmi' methods. The program is implemented through regular steps, including preparation for memorization, submission of memorization to teachers, and regular evaluation. Since its implementation in 2017, this program has received full support from the madrasah and students' parents. The positive effects of the program can be seen in the students' cognitive aspects, which tend to be stable and even improve, as well as in the development of good character, such as discipline, a sense of responsibility, and love for the Qur'an.The findings of this study indicate that the tahfidz program can be implemented effectively in the context of formal education as a way to produce a generation with broad knowledge and commendable morals.